COMMODIFICATION OF KNOWLEDGE IN THE DIGITAL ECOSYSTEM: A LITERATURE STUDY ON SHIFTING ACCESS TO EDUCATION AND THE SOCIAL JUSTICE EMERGENCY CRISIS - Zein Faizin; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This literature study research analyzes the phenomenon of knowledge commodification in the digital education ecosystem and its implications for access to education and social justice. The rapid transition to educational technology (EdTech) and platform-based learning has shifted the paradigm of education from a public good to a highly commercialized digital commodity. This research aims to evaluate the trend of digital privatization in education, examine the shift in access to learning materials, and respond to emerging education equity emergencies. Using a qualitative literature matrix methodology, data were collected from 20 reputable academic journals published in the last five years, national education statistics reports, and critical sociological frameworks integrated with Islamic educational values. The results show that market-driven digital platforms exacerbate the "digital abyss" and create stratified access to quality education, where premium knowledge is hidden behind paid walls. The study also integrates the Qur'anic instructions on justice in the dissemination of knowledge, and argues that commercial exclusivism violates fundamental human rights in education. The research concludes that the commercialization of digital education poses a critical threat to social justice, thus requiring a strict regulatory framework and institutional commitment to openly accessible public pedagogy.